AN APPRAISAL OF THE CAPACITY OF GOVERNMENT INSTITUTIONS FOR BORDER MANAGEMENT IN NIGERIA - Oji, Okechukwu Richard; Mustapha, Fatima (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
The paper reviews and analyses national security challenges in relation to border governance in Nigeria, which are made more complex by poverty, lack of good governance, corruption, chronic armed conflicts, armed banditry, porous borders and transnational crimes. Border issues or boundary politics remains an integral part of the peoples, livelihood, economic activities, regional cooperation, territorial integrity and sovereignty of any nation. As such, every approach to its management and proper settlement should take all the risks and benefits of border relationships into account. Border disputes often arises from challenges of territorial allocation which are evident in terms of border claims or relevance of borderlands to neighbouring states in terms of its historical, geographical, ethnic, cultural, economic, military or strategic importance. Borderlands security and management in terms of location, interaction patterns and transitional features have in recent times created a vacuum in Nigeria’s border policy and Architecture. The paper identities these problems and proffer solutions towards enhancing the capacity of Government Institutions in Border Management in Nigeria.